Impact of Collaborative Marketing on Vegetable Production Systems: the Case of Clustering in the Southern Philippines - Real, R.; Concepcion, S.; Montiflor, M.; Axalan, J.; Lamban, R.; Apara, D.; Israel, F.; Bacus, R.; Batt, Peter; Murray-Prior, Roy; Rola-Rubzen, Maria Fay (International Society of Horticultural Science, 2013)
In the Southern Philippines, the clustering method has been introduced to smallholder vegetable farmers as a development approach to facilitate linkages with markets, while simultaneously assisting farmers to establish more organized and effective groups. For the clusters to sustain their linkages with buyers, they must often adapt their production systems to meet the buyers’ requirements. This study explores the impact of cluster marketing on vegetable production systems in the Southern Philippines. Key changes in the production systems include the use of superior varieties to increase the marketable yield and to mitigate disease, the introduction of protected cropping through rain shelters to minimize losses from adverse climatic conditions, and the application of non-chemical inputs to reduce production costs.